Eficiência nos processos de produção, beneficiamento e comercialização de sementes de soja da empresa Agro Silo Santa Catalina S.A. (Semillas Veronica®) - Câmara, Alicia Magdalena González (2012)
One of the main factors that ensure agricultural productivity is the use of quality seeds, in this sense the Agro Silo Santa Catalina invests in production and marketing of seeds. The present study was to determine the efficiency in production processes, post-harvest technology and marketing of soybean seeds in the company of Veronica Seeds Agro Silo Santa Catalina S.A., the region of Alto Paraná - Paraguay. The company produces its own soybean seed through cooperatives with adequate technological capacity. The database of the study, covering the years 2005/06 to 2009/10, consisted of: 1- Area established for seed production, 2- Quantity harvested seed crude, 3- Quantity seeds cleaned and classified, 4- Number of seed approved for marketing; 5- Quantity of seed sold. Regarding the area of cultivation and harvest to their respective seed, we calculated the percentage of the gross amount of seed in relation to benefit and the amount approved for marketing and effectively performed. Records were obtained from the company itself by selecting from the year 2005/06 for all cultivars produced by the company. Based on the information found to be: The efficiency of production of soybean seeds varies throughout the year of production. Dispose of seeds in the stage of processing has an average of 30%, which indicates the need to monitor and control the conduct of the field and at harvest. The company plans to align production with sales plans. There is a need to improve the system of internal quality control.